Pengaruh Consumer Education Dan Service Quality Terhadap Kepuasan Dan Loyalitas Pasien Rawat Inap (Studi Pada Rumah Sakit Umum Swasta di Kota Medan) - Lubis, Arlina Nurbaity (Jurnal Aplikasi Manajemen, 2009)
The progress of business world has noted an amazing development, especially in the service industry that has dominated the market competition. In Indonesia, the service sector has had a fast development as well. It can be seen from the distribution of PDB`s percentage according to business field, showing that the contribution of service sector comes near 50%. One kind of the service industry having a fast development is hospital industry. Along with the development of the globalization of World Trade and the agreement of ASEAN Free Market 2003, APEC 2010, and The World Free Market 2020, therefore the hospital have to start to plan quality improvement program and service given, so that it can vie in this very competitive climate. This research takes the sample in 4 Private Public Hospitals Type B in Medan. They are RSU Haji, RSU Permata Bunda, RSU Methodist, and RSU Herna, with 235 respondents. The research data are primary data, obtained through interviews, observations, and the answering of questionnaires with scale Likert 1-5 to know the respondent`s perception to examined variables, and hospital secondary data documented in the form of reports and brochures. The research data is analyzed with Structural Equation Modelling (SEM) with software AMOS. The result of the analysis shows that consumer education directly effect toward satisfaction, but not loyalty. However, indirectly it has effect toward loyalty through satisfaction. Service quality directly effect toward satisfaction and loyalty. Besides, service quality has effect toward loyalty through satisfaction, furthermore, satisfaction directly effect toward loyalty.